The Anti-atherosclerotic Effects of Natural Polysaccharides: From Phenomena to the Main Mechanisms of Action - P. Karagodin, Vasily; I. Summerhill, Volha; Yet, Shaw-Fang; Orekhov, Alexander N. (Current Pharmaceutical Design, 2022)
Polysaccharides (PSs) of plant origin have a variety of biological activities, including antiatherosclerotic, but their use in atherosclerosis therapy is hindered by insufficient knowledge based on the cellular and molecular mechanisms of action. In this review, the influence of several natural PSs on the function of macrophages, viral activity and macrophage cholesterol metabolism has been discussed, considering the tight interplay between these aspects in the pathogenesis of atherosclerosis. The anti-atherosclerotic activities of natural PSs related to other mechanisms have also been explored. Directions for further research of the antiatherosclerotic effects of natural PSs have been outlined, the most promising of which can be nutrigenomic studies.
Keywords: macrophage cholesterol metabolism